2004
DOI: 10.2131/jts.29.155
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic Effects of .Alpha.-Fluoro-.Beta.-Alanine (Fbal) and Fluoroacetic Acid (Fa) on Dogs

Abstract: In order to clarify the mechanism of the neurotoxicity of 5-FU and/or its masked compounds, we studied the effects of alpha-fluoro-beta-alanine (FBAL) and fluoroacetic acid (FA) on the formation of vacuolar changes in the dog cerebrum, using the dosage of 3.0 mg/kg/day of FBAL-HCl (FBAL x HCl) and 0.03 mg/kg/day of FA-Na (FA x Na), respectively. These 2 compounds were selected because they are the metabolites of 5-FU claimed to be responsible for the neurotoxic effects of 5-FU and/or its masked compounds, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 18 publications
(19 reference statements)
1
24
0
Order By: Relevance
“…14 Studies in dogs examining the mechanism leading to neurotoxicity associated with 5-FU suggest that this medication may lower brain GABA concentration secondary to inhibition of the citric acid cycle by fluorocitrate. 13 Because benzodiazepines potentiate the action of GABA, this may explain why most case reports describing management of 5-FU toxicosis in dogs suggest that seizures are often refractory to standard therapy. 8,9 Levetiracetam, in contrast, acts by binding the synaptic vesicle 2a protein on the presynaptic terminal, thereby limiting synaptic vesicle fusion and neurotransmitter release; the drug does not facilitate the action of GABA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Studies in dogs examining the mechanism leading to neurotoxicity associated with 5-FU suggest that this medication may lower brain GABA concentration secondary to inhibition of the citric acid cycle by fluorocitrate. 13 Because benzodiazepines potentiate the action of GABA, this may explain why most case reports describing management of 5-FU toxicosis in dogs suggest that seizures are often refractory to standard therapy. 8,9 Levetiracetam, in contrast, acts by binding the synaptic vesicle 2a protein on the presynaptic terminal, thereby limiting synaptic vesicle fusion and neurotransmitter release; the drug does not facilitate the action of GABA.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 More recent studies in dogs have implicated the metabolites fluoroacetate and ␣-fluoro-␤-alanine as causative agents for the observed neurotoxicosis. 13 Several retrospective case series in the veterinary literature describe the outcomes associated with 5-FU toxicosis in dogs. One case series reported that 5 of 13 dogs treated with 5-FU intravenously at a dose of 10 mg/kg for various neoplasms developed neurotoxicosis; all but one of those affected dogs died.…”
mentioning
confidence: 99%
“…It was also found that a series of other compounds metabolize to FA as intermediate products: these are the anticancer drugs 5-fluorouracil and fluoroethyl nitrosourea, N-(2-fluoroethyl) derivatives of the narcotic analgesics normeperidin and normetazocin, the industrial chemicals fluoroethanol and 1-(di)halo-2-fluoroethanes (Yamashita et al, 2004;Arellano et al, 1998;Yeh and Cheng, 1994;Reifenrath et al, 1980;Tisdale and Brennan, 1985;Tecle and Casida, 1989;Keller et al, 1996;Feldwick et al, 1998). Finally, industrial 'achievements' have led to the appearance of FA in fog and rain (Rompp et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies in cats showed two types of neuropathological changes induced by FBAL: vacuoles and necrosis/softening-like changes similar to those found in patients following orally administered 5-FU [29]. These neurotoxic effects of FBAL and fluoroacetic acid, another metabolite of 5-FU degradation, were also confirmed in dogs [30]. …”
Section: Gimeracilmentioning
confidence: 80%